DEVELOPMENT OF INTERACTIVE VIDEO BASED ON LOOMIE LIVE APPLICATION ASSISTED BY NEARPOD AS LEARNING MEDIA ON THE SUBJECT OF CHEMICAL BONDS - Haetami, Aceng; Karsita, Elma; Maysara, Maysara; Dahlan, Dahlan; Esnawi, Esnawi; Arsyad, Muhammad (LPPM Universitas Jambi, 2026)
The abstract nature of chemical bonding concepts often results in low student engagement and suboptimal learning outcomes, particularly when instruction relies on teacher-centered approaches. This study aimed to develop and evaluate an interactive video learning medium based on the Loomie Live application integrated with Nearpod and structured using the Problem-Based Learning (PBL) model. Employing a Research and Development (R&D) design, the study involved expert validation, small-group trials (n = 9), and field implementation with 30 tenth-grade students. Data were collected using validation sheets, practicality questionnaires, observation sheets, and pretest–posttest instruments, and analyzed using percentage criteria and N-gain scores. The results indicated that the developed media achieved high validity (media aspect = 80.55%; material aspect = 78.27%), very high practicality (teacher response = 92.43%; student response = 95.83%), and strong effectiveness (N-gain = 0.8, high category). Student learning activity reached 84.28%, indicating very active engagement. The novelty of this study lies in the integration of real-time animated video production (Loomie Live) with interactive assessment features (Nearpod) within a PBL framework, enabling synchronous conceptual visualization and formative feedback in chemistry learning. The findings imply that technology-enhanced, problem-based interactive video can significantly improve conceptual understanding and learner engagement in abstract science topics. This model offers a scalable digital learning innovation adaptable to secondary chemistry education contexts.